BENEATH THE SURFACE: UNCOVERING THE CONSTITUTIVE WORK PERFORMED BY METAPHORIC CLUSTERS WITHIN THE RACE RHETORIC OF EVANGELICAL MEGACHURCHES - (:unkn) unknown (My University, 2024)
This dissertation contributes to scholarly conversations about race rhetoric, metaphor, and evangelical rhetoric by uncovering the racially-significant constitutive work performed by clusters of metaphors within the race rhetoric of evangelical megachurches. Engaging in metaphoric cluster criticism from a constitutive perspective, I analyze sermon series delivered at three evangelical megachurches in the Twin Cities in the wake of George Floyd’s murder to investigate the crucial role that metaphors play within theological rhetoric. Though these churches profess similar theological commitments to one another, clusters of metaphors mediate those commitments into divergent constitutive guidance regarding how to respond to social issues like race. I propose that space and mobility metaphors play an important role within that mediation by shaping the means and urgency with which religious auditors are invited to respond to a social crisis. Evangelical megachurch sermons merit ongoing attention from rhetorical scholars and scholars of evangelicalism because they contain clusters of metaphors that perform constitutive work that influences how congregations relate to other communities within the context of urgent social justice issues like race.
Keywords: Communication; Rhetoric and Composition; Religion; Constitutive Rhetoric; Evangelicalism; Megachurch; Metaphor; Pastoral Rhetoric; Race